A Conversation with Mike Breen - Rodríguez Elizabeth (Universidad Nacional de Colombia, 2001)
The Process Syllabus, (Breen 1989) as its name suggests, is a 'process plan' that tries to serve the joint creation and implementation of a syllabus by providing a framework for planning and action that should emerge from decisions jointly made by teachers and learners during the classroom learning experience. Due to its nature, it goes beyond a "propositional" syllabus like the ones known as Functional or Task-based . Therefore, the Process Syllabus, providing a plan and a bank of resources, and requiring regular reflective and formative evaluation, facilitates the learners' creation of their own syllabus in an on-going and adaptive way